Automaton extensions of mappings on the set of words defined by finite Mealy automata - Osys, M. (Algebra and Discrete Mathematics, 2005)
The properties of an automaton extensions of mappings on the set of words over a finite alphabet is discussed. We obtain the criterion whether the automaton extension of given mapping if defined by a finite automaton.